2003
DOI: 10.1093/toxsci/kfg096
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gene Expression during Rat Wolffian Duct Development in Response to in Utero Exposure to the Antiandrogen Linuron

Abstract: Linuron is an herbicide with weak androgen receptor (AR) antagonist activity. Exposure to linuron from gestation days (GD) 12 to 21 perturbs androgen-dependent male reproductive development. In utero exposure to 50-mg/kg/day linuron induces malformations of the epididymis and the vas deferens. The objective of this study was to identify alterations in gene expression within the testis and epididymis associated with abnormal Wolffian duct development and to correlate changes in gene expression with the gross mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 53 publications
1
38
0
1
Order By: Relevance
“…This is in agreement with previous studies showing that exposure to antiandrogenic compounds in utero results in a high frequency of epididymal malformations when studied in adulthood (17,23,26,27,34). Exposure to LW-flutamide did not result in incomplete WDs at any time point studied.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previous studies showing that exposure to antiandrogenic compounds in utero results in a high frequency of epididymal malformations when studied in adulthood (17,23,26,27,34). Exposure to LW-flutamide did not result in incomplete WDs at any time point studied.…”
Section: Discussionsupporting
confidence: 93%
“…For example, loss of epididymal coiling was reported in rat embryos exposed to Di(nButyl) phthalate, which caused a decrease in androgen biosynthesis (36). Similarly, embryos exposed to linuron, a weak AR antagonist, also exhibited decreased epididymal coiling (37). Based on these observations, we initially speculated that the loss of epididymal coiling in the InhbaϪ/Ϫ mutant was the result of defects in systemic androgen production, instead of a direct local effect of Inhba.…”
Section: Parameters Of Androgen Action Are Not Affected In the Absencmentioning
confidence: 96%
“…Testosterone reaching the Wolffian duct by the luminal compartment up regulates AR levels and induces proliferation of the epithelial cells through mesenchymal-epithelial cell interactions involving paracrine factors (48). At this stage, growth factors and components of the extracellular matrix are proposed to be important mediators from the mesenchyme to the epithelium (49). Recently, it has been suggested that circulating androgens are also important to induce Wolffian duct stabilization and subsequent formation of epididymides, as well as prostatic bud formation, virilization of the urogenital sinus and prostatic development (50).…”
Section: Expression and Physiological Roles Of Androgen Receptor In Tmentioning
confidence: 99%